2018
DOI: 10.1016/j.jdermsci.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing allows the identification of two novel groups of Xeroderma pigmentosum in Tunisia, XP-D and XP-E: Impact on molecular diagnosis

Abstract: To our knowledge, this is the first study that identifies XP-D and XP-E complementation groups in Tunisia. These two groups are very rare and under-diagnosed in the world and were not reported in North Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Due to the high frequency of consanguineous unions, this region harbors many rare recessive genetic diseases (Romdhane et al, 2012). Regarding XP in this region, we observed a high frequency of XP-A patients carrying the p.R228 ∗ mutation presenting with a severe neurological phenotype, moreover a few families manifest mild forms of the disease like XP-D (Ben Rekaya et al, 2018). The emergence of an XP-G form that we identified here is also likely due to the high rate of consanguinity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Due to the high frequency of consanguineous unions, this region harbors many rare recessive genetic diseases (Romdhane et al, 2012). Regarding XP in this region, we observed a high frequency of XP-A patients carrying the p.R228 ∗ mutation presenting with a severe neurological phenotype, moreover a few families manifest mild forms of the disease like XP-D (Ben Rekaya et al, 2018). The emergence of an XP-G form that we identified here is also likely due to the high rate of consanguinity.…”
Section: Discussionmentioning
confidence: 89%
“…The mutations with founder effect responsible for the XP-C (Ben Rekaya et al, 2009) and XP-A phenotypes (Messaoud et al, 2010) have been also found in other North African countries (Soufir et al, 2010) such as Morocco (Senhaji et al, 2013; Kindil et al, 2017), Egypt (Amr et al, 2014), Algeria (Bensenouci et al, 2016), and Libya (unpublished data). The XP-D and XP-E forms have been recently identified thanks to whole exome sequencing (WES) technology (Ben Rekaya et al, 2018). Patients belonging to these last two groups had mild dermatological manifestations, absence of neurological anomalies, and late onset of skin tumors.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only 17 XP-E patients have been reported until now [12][13][14]. The mutations of DDB2 identified in all XPE patients are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified the fisrt cases of complementation groups XP‐D and XP‐E in Tunisia and in North Africa. Pathogenic variants within the ERCC2 and DDB2 genes segregated in all affected family members (Ben Rekaya et al., ).…”
Section: Xeroderma Pigmentosum and Other Skin Disordersmentioning
confidence: 99%